Caffeic acid attenuates the autocrine IL-6 in hepatocellular carcinoma via the epigenetic silencing of the NF-κB-IL-6-STAT-3 feedback loop1. Issue 65 (16th July 2015) - Wang, Lingling; Lu, Ming; Yi, Mei; Chen, Lijun; Shen, Jian; Li, Zhong; Li, Lei; Yang, Ye; Zhang, Jianping; Li, Yuan
<x xml:space="preserve">Abstract</x> Our study revealed a novel mechanism in CaA-attenuated autocrine IL-6 through the epigenetic silencing of the NF-κB-IL-6-STAT-3 feedback loop in HCC cells.